2023
DOI: 10.1007/s11538-023-01144-5
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Age of Onset of Resistance to Infectious Disease

Abstract: Many organisms experience an increase in disease resistance as they age, but the time of life at which this change occurs varies. Increases in resistance are partially due to prior exposure and physiological constraints, but these cannot fully explain the observed patterns of age-related resistance. An alternative explanation is that developing resistance at an earlier age incurs costs to other life-history traits. Here, we explore how trade-offs with host reproduction or mortality affect the evolution of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These typically consider a population where an already established strain, the 'resident', circulates and assesses the ability of a newly introduced strain, generally called the 'mutant' (or variants in the SARS-CoV-2 case), to replace it [Geritz et al 1998;Brännström, Johansson, and Von Festenberg 2013]. One of the strong assumptions made by many of these frameworks that we need to alleviate is that of the separation between epidemiological and evolutionary timescales, meaning that the resident is assumed to reach an epidemiological equilibrium before the mutant appears [Brännström, Johansson, and Von Festenberg 2013;Buckingham and Ashby 2023]. In the SARS-CoV-2 pandemic, for example, such an equilibrium has not yet been reached since variants with different traits still emerge frequently (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…These typically consider a population where an already established strain, the 'resident', circulates and assesses the ability of a newly introduced strain, generally called the 'mutant' (or variants in the SARS-CoV-2 case), to replace it [Geritz et al 1998;Brännström, Johansson, and Von Festenberg 2013]. One of the strong assumptions made by many of these frameworks that we need to alleviate is that of the separation between epidemiological and evolutionary timescales, meaning that the resident is assumed to reach an epidemiological equilibrium before the mutant appears [Brännström, Johansson, and Von Festenberg 2013;Buckingham and Ashby 2023]. In the SARS-CoV-2 pandemic, for example, such an equilibrium has not yet been reached since variants with different traits still emerge frequently (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…(2014), who found that these models do not typically generate diversity through polymorphism or cycling (Best et al 2014). The evolution of host resistance in age-structured populations has been theoretically explored (Ashby and Bruns 2018; Buckingham et al 2023; Buckingham and Ashby 2023), but as far as we are aware, the (co)evolution of age-structured tolerance and virulence has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%